Konsep Fiqh al-Maālāt Dan Urgensinya Dalam Konstruksi Hukum Islam : Studi Analisis Terhadap Fatwa Majelis Ulama Indonesia Tentang Pernikahan Beda Agama - Rachmadhani, Fajar (MAQASID, 2024)
Abstract This study aims to analyze the fatwa of the Indonesian Ulema Council (MUI) regarding the phenomenon of interfaith marriage in Indonesia, which is currently a hot issue and is often discussed and even debated. The theory used to analyze the fatwa is the theory of the concept of maālāt al-af'āl, which is an approach used to predict and glance at the possible consequences that will arise from an act. This qualitative research focused on library research which is descriptive-analytical based on text studies. In this case, the researcher uses the fatwa of the Indonesian Ulema Council (MUI) on interfaith marriage as primary data. In comparison, the secondary data were from fiqh books, ushul fiqh, and maqaşid as-syarī'ah. This study uses a content analysis approach (content analysis). This method was used to draw conclusions through efforts to bring up the characteristics of the message, which was carried out objectively and systematically. The results show that the Indonesian Ulema Council (MUI) forbids interfaith marriages absolutely, both non-Muslim men marrying Muslim women or Muslim men marrying Ahl al-Kitāb women, although the majority of madzhab scholars are of the opinion that it is permissible to marry Ahl al-Kitāb women for Muslim men. This shows that the Indonesian Ulema Council (MUI) has theoretically and practically implemented the concept of maālāt al-af'āl in the process of ijtihād and the adoption of Islamic law by predicting the impact of the marriage, such as the emergence of various problems in the household such as the implementation of worship, the future of beliefs and children's education, food arrangements, and practices related to religious traditions. Keywords: Fiqh al-Maalāt, Fatwa, MUI, Interfaith Marriage.